Compensation Management - Rupus Rupus; Ade Febrianto (CAKRAWALA : Management Science Journal, 2025)
Compensation management is an important aspect of human resource management which aims to reward employees for their contributions to the organization. Compensation can be financial or non-financial and increases employee motivation, performance and job satisfaction. This article discusses compensation policies, the factors influencing them, and the implications for employee productivity. Using a literature review method, this article presents various theoretical and empirical perspectives related to compensation management.